Adsorption kinetics of reactive dye using agricultural waste: banana stem. Issue 1 (3rd November 2021) - Arun Kumar, K.; Bharath, M.; Krishna, B. M.
Abstract: Removal of color from dye-bearing water has been a bothering task from the health point of view and in the aesthetic sense as well. Finding out the effectiveness of Remazole Red RGB dye removal is the aim of the present work using banana stem, an agricultural waste, as an activated carbon. The preparation of the banana stem activated carbon was done in the laboratory by carbonization followed by activation. To assess the impact of varied exploratory variables such as pH of adsorbate, contact time, initial dye concentration and dosage of adsorbent on the removal of Remazole Red RGB dye from aqueous solution adopting batch studies were performed. The Freundlich and Langmuir isotherm models were used to predict the adsorption capacity of adsorbent at equilibrium conditions, the kinetic parameters were also determined. The concentration of dye remaining in the system was measured using a UV visible spectrometer. The batch test resulted in the removal of the maximum of 87% of dye when the dye concentration was 2 mg/L, at an adsorbent dose of 0.5 gm/L and dye pH 4 in 35 minutes. It is established from the studies that the equilibrium data suited excellently both Freundlich and Langmuir isotherms. The maximum adsorption capacity of 14.28 mg/L was established from the Langmuir isotherm model. To state the sorption kinetics, pseudo-first-order and pseudo-second-order kinetic models were evaluated. The intraparticle diffusion model was checked for the adsorption data and it was observed that intraparticle diffusion is not the only rate-limiting step. The regression analysis results indicated that the linear regression model gave the best results. The above detection exhibits that banana stems can be used productively for the removal of color from dye-containing wastewater. HIGHLIGHT: Removal of color from dye bearing water has been a bothering task from the health point of view and in the aesthetic sense as well. Finding out the effectiveness of Remazole Red RGB dye removal is the aim of the present work using banana stem an agricultural waste as an activated carbon. The preparation of the banana stem activated carbon was done in the laboratory by carbonization followed by activation.